2020
DOI: 10.1590/1806-9282.66.5.623
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of postoperative risk of complications on inguinal hernioplasty and its relation to risk factors

Abstract: SUMMARY INTRODUCTION Abdominal wall hernias are a highly prevalent pathology, considering that 55 percent of the world population is affected by this disease at some point in their lives. As a large part of these patients present comorbidities, it is important to correlate the incidence of complications with the presence of previous pathologies. OBJECTIVES To evaluate whether the presence of comorbidities in patients submitted to inguinal hernioplasty increases the risk of acute and chronic complications i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
0
1
2
Order By: Relevance
“…Other complications were pain on exertion, wound seroma and wound hematoma. These findings are in agreement with results of recent retrospective study conducted by Chibata and Daronch in Brazil on records of 313 patients with inguinal hernia [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other complications were pain on exertion, wound seroma and wound hematoma. These findings are in agreement with results of recent retrospective study conducted by Chibata and Daronch in Brazil on records of 313 patients with inguinal hernia [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hypertension is considered a risk factor in surgical intervention in the groin region [11]. However, in our study, hypertension was not identified as a significant risk factor for groin complications.…”
Section: Discussioncontrasting
confidence: 71%
“…Palabras claves: apéndice cecal, apendicitis, herniorrafia, hernia inguinal L as hernias de la pared abdominal representan un problema de salud a nivel mundial, con una prevalencia de 1,7% para todas las edades 1 . La Hernia Inguinal (HI) en relación con todas ellas constituye del 60 al 75% [1][2][3] , y el riesgo de ocurrencia en el hombre es de 27 al 43%, mientras en mujeres es solo del 3 al 6% [3][4][5] . Los grupos de edades más afectados se encuentran entre los 30 a los 59 años 3 .…”
Section: Introductionunclassified
“…Los grupos de edades más afectados se encuentran entre los 30 a los 59 años 3 . El tratamiento quirúrgico efectuado con más frecuencia en todo el mundo es la hernioplastia inguinal 2,5 . Cuando la HI no es corregida, puede volverse gigante al extenderse por debajo de la mitad del muslo en posición de pie [3][4][5][6][7][8][9] .…”
Section: Introductionunclassified